EMBRACING INDIGENOUS WISDOM: HARNESSING INDIAN KNOWLEDGE SYSTEMS TO CONSERVE BIODIVERSITY - Lata, Parvesh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In an era marked by escalating environmental degradation and loss of biodiversity, there is a growing recognition of the invaluable contribution that indigenous knowledge systems can offer to conservation efforts. This research paper explores the profound Indian Knowledge Systems (IKS) and their invaluable potential in contributing to biodiversity conservation. The paper underscores the significance of harmonizing age-old wisdom with contemporary conservation strategies to achieve sustainable environmental stewardship. The primary objective of this study is to accentuate the pertinence of IKS in shaping effective policies and practices for preserving biodiversity. By doing so, it advocates for a more inclusive and holistic approach to environmental conservation. Drawing upon a diverse array of indigenous practices, beliefs, and insights, this study delves into the rich tapestry of Indian Knowledge Systems, highlighting their profound potential in the preservation and restoration of biodiversity. Through a comprehensive analysis of key components of IKS, including traditional ecological knowledge, customary practices, and spiritual beliefs, this paper aims to underscore the relevance and applicability of indigenous wisdom in shaping effective policies and practices for biodiversity conservation. It advocates for a paradigm shift towards a more inclusive and culturally sensitive approach to environmental management, one that acknowledges and respects the wisdom of indigenous communities. Furthermore, this study examines the challenges and opportunities associated with the integration of IKS into mainstream conservation efforts, highlighting the need for collaboration, knowledge exchange, and mutual respect between indigenous peoples and external stakeholders. It emphasizes the importance of empowering indigenous communities as custodians of their traditional territories and knowledge systems, fostering a sense of ownership and agency in conservation initiatives. This paper advocates for the harnessing of Indian Knowledge Systems as a powerful tool for biodiversity conservation, offering insights and lessons that can inform and inspire global efforts towards a more sustainable and harmonious relationship between humanity and the natural world.